Public service awareness (PSA) on promoting healthy nutrition knowledge for primary school students through paper cut stop motion animation - Lim May Lee (2017)
Previous report in BMC Public Health (2009) mentions that obesity is increasing from 9.7% to 1.36% since 2001 to 2008.Moreover,Malaysian children are more overweight and the incidence of chronic illness is higher than any time in our nation’s history. Besides, this study has identified the alternative techniques which can be used to produce new designs of healthy eating campaign among primary school students as their guide and information about food take properly. Stop motion as a media will be use to promote healthy nutrition knowledge at primary school. Information about healthy habits can provide effectively through Public Service Awareness (PSA).This study describe the primary school students understanding on eating healthy through the stop motion as a media on increasing healthy nutrition knowledge. This research aim to determine paper cut stop motion as a media on increasing healthy nutrition knowledge at primary school. This study use qualitative and quantitative questionnaire for 30 primary school students at Kelantan. Result from the pilot test demonstrate that the 80% of primary school students agreed that media can increasing healthy nutrition knowledge effectively.Based on student's understanding frequencies,90% of them more like watching cartoon and animation.In addition, effective ways of preventing and controlling levels of obesity are urgently needed,and a good place to start is with young children who are starting school.In conclusion,this study is to explore the alternative techniques which can be used to increasing healthy eating among primary student as their guide and information about food intake properly.